PELATIHAN PENGELOLAAN BAHAN BAKU HAYATI MENJADI PUPUK ORGANIK UNTUK MENINGKATKAN PRODUKTIVITAS PADA KELOMPOK TANI ARIH ERSADA DESA AJI JULU KECAMATAN BERASTAGI - Yolanda, yola; Suci Pertiwi; Purnaya Sari Tarigan; Anita Tarihoran (Jurnal Pengabdian Bukit Pengharapan, 2023)
The Agricultural Research and Development Agency has an important and strategic role in producing technological innovations and agricultural institutions in an effort to accelerate Indonesia's economic development. This real role is realized through improving the quality of production through the manufacture of fertilizers using biological raw materials so that farmers can save on production costs. Based on the results of a survey that was conducted, the Arih Ersada farmer group in Aji Julu Village, Kec. Berastagi Regency Karo, farmers tend to buy fertilizer for their plants, resulting in high production costs and making crop productivity not optimal if farmers have difficulty purchasing fertilizer. Training on processing biological raw materials into organic fertilizer for farmers in Aji Julu Village, Kec. Berastagi is expected to provide additional knowledge for farmers in the use of biological raw materials in the manufacture of organic fertilizers so that farmers can save production costs and increase agricultural productivity. As well as farmers can understand what role is needed in an effort to improve welfare as farmers and in the end can increase economic growth in their region. This counseling aims to increase a broader understanding of the role of farmers as entrepreneurs so that farmers are not trapped in the production framework but more broadly into other aspects such as producing their own organic fertilizer